Sustainable Tourism Development Through Social Empowerment - Fitriaty, Fitriaty; Rosita, Sry; Fazri, Andang; Saputra, Muhammad Haris (Universitas Mercu Buana, 2025)
Objectives: This research aims to develop a sustainable tourism development model through social empowerment, prioritizing local wisdom, infrastructure, and Human resources management strengthened by government rule.Methodology: This study uses a quantitative approach by distributing questionnaires to 270 tourists using convenience sampling techniques, who visiting the main destinations in Jambi province consisting of 9 districts and 2 cities and the data is processed using smart PLS, a qualitative method by conducting Focus Group discussions to obtain validation of the findings of the research results that are adjusted to the facts from the opinions of experts.Finding: This study found that local wisdom and human resource management significantly influence sustainable tourism development, while infrastructure does not directly contribute to tourism sustainability. Social empowerment plays a crucial role in strengthening the relationship between local wisdom, infrastructure, and human resource management through government rule.Conclusion: The key implication of these findings underscores the importance of effective social empowerment and governance in ensuring the long-term sustainability of the tourism sector. Therefore, policies that encourage active participation of local communities in tourism management should be developed, supported by training and capacity-building programs to enhance workforce adaptability to market and technological changes. Tourism industry players in Jambi to integrate local wisdom into business models and destination management to enhance attractiveness and sustainability. Further research is needed to explore more effective mechanisms for strengthening social empowerment and tourism governance through community-based approaches, as well as to examine the impact of fiscal policies and economic incentives on tourism sustainability. Overall, this study highlights the necessity of collaboration between governments, local communities, and private sector stakeholders to build a resilient and sustainable tourism ecosystem.